Aconiti Lateralis Radix Praeparata as Potential Anticancer Herb: Bioactive Compounds and Molecular Mechanisms - Zhang, Wen; Lu, Chaoying; Cai, Shuhui; Feng, Yaru; Shan, Jinjun; Di, Liuqing (Frontiers in Pharmacology, 2022)
Aconiti Lateralis Radix Praeparata (Fuzi in Chinese) is a traditional herbal medicine widely used in China and other Asian countries. Fuzi extracts and its active ingredients exert considerable anticancer, anti-inflammatory and analgesic effects. Alkaloids and polysaccharides, the main components in Fuzi, are responsible for its anticancer activities. The current review would focus on the active constituents and their antineoplastic efficacies by inducing apoptosis, inhibiting migration, regulating immunity, affecting metabolism as well as reversing multidrug resistance. Collectively, alkaloids and polysaccharides in Fuzi might be potential new drugs with multi-functional activities for cancer treatment.